Synthesis and design of ligand copper complexes as anti-inflammatory drugs - Elmagbari, Fatin M Ali (Department of Chemistry, 2015)
Rheumatoid arthritis is a debilitating disease for which there is no cure. Copper has been used for centuries to alleviate the inflammation associated with the disease. The aim of this research was to design and test new ligands which are able to promote the percutaneous absorption of copper and/or mobilize endogenous copper reserves. Formation constants of H+, Cu(II), Ni(II) and Zn(II) with five low molecular ligands 2-((2-aminoethyl)amino)-N-(pyridin-2- ylmethyl)acetamide) [H(555)NH2], 2-((2-dimethyl-amino)ethyl)amino)-N-(pyridin-2-ylmethyl) acetamide [H(555)NMe2], N-(2-aminoethyl)-N'-(pyridin-2-ylmethyl)ethanediamide [H2(555)NH2], 3-(2-aminoacetamido)-N-(pyridin-2-ylmethyl)propanamide [H2(565)NH2], 3-amino-N-(pyridin-2-lmethyl)-propanamide [H(56)NH2] were measured at 25±0.01oC and at an ionic strength of 0.15M (NaCl) using glass electrode potentiometry. The structures of the different Cu(II) species formed with these ligands were investigated using ultraviolet-visible (Uv-visible), nuclear magnetic resonance (NMR) spectroscopy and X-ray crystallography as well as molecular mechanics calculations. The Uv-visible spectra obtained for the different species in solution were typical of tetragonally distorted Cu(II) complexes. The active binding sites were identified as the pyridine nitrogen, the amide nitrogen and the terminal amino group. The pyridine nitrogen was involved in coordination first, followed by the amide and then the terminal amine groups. The X-ray crystal structure of two of the Cu(II) complexes were solved; one formed a rectangular pyramidal geometry and the other a distorted square planar geometry. Molecular mechanics was used to determine the lowest energy conformation of different possible geometries. Since the preferred route of administration is through the skin, the rate of dermal absorption and the bioavailability of copper are important. For this reason, the drugs were designed so that they could be administered dermally and be selective for Cu(II) so that they do not affect the speciation of other metal ions in blood plasma. Speciation calculations using a blood plasma model were used to estimate the complexing ability of the ligands in vivo. This result showed that [H(555)NH2] was the best at mobilising copper in vivo.